Organizations behaving badly : destructive behavior and corrective responses - Svyantek, Daniel J. (Research in organizational analysis., 2021)
"Organizational science profits from taking new perspectives that using a simple model to understand why behaviors of particular types occur within them. This volume provides readers with a rich source of case-studies and empirical studies of the role played by the interaction between individual actors, organizational contexts, and the actual behaviors being performed the actors. These chapters each seek to describe how these three interact in to create organizational practices with negative effects on either internal members of the organization or external stakeholders (e.g,. clients). The chapters provide insight into how organizations may control these negative behaviors with basic Human Resource Management practices. It is this volume's hope that these chapters may provide insight into the important role these three factors plays in understanding negative organizational behavior within organizations across the world"--